Peptide YY (PYY) Is Expressed in Human Skeletal Muscle Tissue and Expanding Human Muscle Progenitor Cells - Gheller, Brandon J.; Blum, Jamie E.; Merritt, Edward K.; Cummings, Bethany P.; Thalacker-Mercer, Anna E. (Frontiers in Physiology, 2019)
Peptide YY (PYY) is considered a gut peptide with roles in post-prandial appetite and glucose regulation. Circulating PYY protein levels increase during aerobic exercise. Furthermore, people who have greater increases in muscle progenitor cells (hMPCs), the adult stem cell population responsible for skeletal muscle (SkM) repair, after resistance training have higher PYY transcript levels in SkM prior to training. Currently, examination of PYY expression patterns in SkM and/or hMPCs is lacking. Our objective was to identify the expression patterns of PYY in SkM and hMPCs. PYY and the associated Y receptors were analyzed in SkM biopsy tissue and cultured hMPCs from young and old human participants. Additional experiments to assess the role and regulation of PYY in hMPCs were performed. In SkM, PYY and one of the three Y receptors (Y1r) were detectable, but expression patterns were not affected by age. In expanding hMPCs, PYY and all three Y receptor (Y1r, Y2r, and Y5r) proteins were expressed in a temporal fashion with young hMPCs having greater levels of Y receptors at various time points. Exogenous PYY did not affect hMPC population expansion. hMPC PYY levels increased following the metabolic stimulus, 5-Aminoimidazole-4-carboxamide ribonucleotide (AICAR), but were not affected by the inflammatory stimulus, tumor necrosis factor alpha (TNF). In conclusion, PYY and Y receptor expression are not impacted by age in SkM tissue but are reduced in old vs. young expanding hMPCs. Furthermore, PYY production is stimulated by low energy states potentially as a compensatory mechanism to maintain hMPC population expansion.